Gambaran Pengisian Pada Formulir Catatan Perkembangan Pasien Terintegrasi Di Rumah Sakit Yadika Kebayoran Lama - Gama Bagus Kuntoadi; Ai Purwati (APIKES Bhumi Husada Jakarta, 2022)
The integrated patient progress record is the documentation of care professionals about the progress of the patient's condition in an integrated form in the standard format in the patient's medical record. The general purpose of this study was to analyze the filling of medical care results on the integrated patient development record form at Yadika Kebayoran Lama Hospital. While the specific objectives are to identify policies and standard operating procedures in the implementation of filling out the results of medical care on the integrated patient progress record form, identify incomplete filling of the integrated patient progress record form and identify the factors causing the incomplete filling of the integrated patient progress record form. This research uses a descriptive method. From the results of the quantitative analysis of research on the completeness of filling out the integrated patient development record form for the period October to December 2018 with a sample of 180, it is known that 90% are incomplete and 10% are filled. The highest incomplete patient identity component consists of medical record number and patient gender with a percentage of 33.4%. In the important note’s component, it was found that 100% of the forms were filled out. The highest incomplete authentication component is the doctor's signature with a percentage of 44.5%. In the component of good notes, the highest is in the